IMPLEMENTATION OF PROBLEM-BASED LEARNING METHODS IN ISLAMIC EDUCATION TO STRENGTHEN STUDENTS' CRITICAL THINKING SKILLS AT THE SIMALUNGUN STATE ISLAMIC SCHOOL - Faisal Hamid; Mhd. Habibu Rahman (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) method in Islamic Religious Education and its contribution to strengthening students' critical thinking skills at MA Negeri Simalungun. This study uses a qualitative approach with a descriptive design. Data were obtained through classroom observation, interviews with teachers and students, and documentation of learning tools and evaluation results. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing, with data validity maintained through source and technique triangulation. The results showed that the application of PBL in Islamic Religious Education learning can be carried out systematically through the stages of problem orientation, group discussion, investigation, presentation of results, and reflection. The implementation of PBL encourages active student involvement in the learning process and has a positive impact on strengthening critical thinking skills, as evidenced by an increase in students' ability to identify problems, analyze information, evaluate arguments, and draw logical and contextual conclusions based on Islamic values. This study concludes that the Problem-Based Learning method is an effective learning approach to improve the quality of Islamic Religious Education learning and develop students' critical thinking skills in Madrasah Aliyah. Therefore, PBL is recommended as an alternative PAI learning strategy that is relevant to the demands of 21st-century education.